Addressing the tax challenges of e-commerce transactions - Susanna Hartanto (International Journal of Financial, Accounting, and Management, 2020)
Purpose: This study aimed to explore e-commerce taxation in Indonesia including some factors that were supporting and also challenging the implementation of e-commerce taxation Research Methodology: Interviews were conducted from the side of fiscus (Directorate General of Taxation) and taxpayers in e-commerce industry. Data collection used semi-structured interview, observation, and documentation. Data analysis of this research was using descriptive method. Results: The result of this study proves that taxation in e-commerce industry has not been implemented in a good manner. Socialization to e-commerce taxpayers should be conducted in more structured and comprehensive ways. Limitations: The limitation of this study was the amount of interviewees due to time limitation. In future research, the amount of interviewees can be added and split into four types of e-commerce transactions according to Directorate General of Taxation Circular No 62 Year 2013. Contribution: A clear and fair e-commerce tax rules should be prepared in good manner to detect e-commerce transactions by government. Socialization to e-commerce taxpayers should be conducted in more structured and comprehensive ways to collect taxation from e-commerce transactions. Keywords: E-Commerce, Digital taxation, Tax, Unified approach